Petrographic and Geochemical Characteristics of the Rocks Belonging to the Elazig Magmatic Complex in the Geçityaka region (Tunceli) - Sar, Abdullah; Rizeli, Mustafa Eren; Ertürk, Mehmet Ali (TUBITAK, 2022)
In this study, the petrographic and geochemical properties of the rocks belonging to the Geçityaka province (Tunceli) and the surrounding Elazığ Magmatic Complex were investigated. The rocks that are the subject of the study are represented by granite, granodiorite, quartz monzonite and monzodiorite. According to petrographic examinations, equigranular, porphyric, porphyric holocrystalline and poikilitic textures are dominant in the rocks. According to the geochemical data of the whole rock, the magmatics that are the subject of the study show I type granite character and compositional distributions ranging from tholeiitic to shoshonitic. In spider diagrams normalized to the primitive mantle and chondrite, large ion lithophile elements and light rare earth elements are more enriched than high field strength elements and heavy rare earth elements. In the light of the data obtained, the studied magmatic rocks are the product of the intra-oceanic subduction that developed during the northward subduction of the southern branch of the Neotethys Ocean and the post-collisional stage generated subsequently. © 2022, TUBITAK. All rights reserved.
Geçityaka Köyü (Tunceli) Çevresindeki Elazığ Magmatik Kompleksi’ne Ait Kayaçların Petrografik ve Jeokimyasal Özellikleri
Keywords: Elazığ Magmatic Complex; Geochemistry; Petrography; Tunceli